The prolactin and growth hormone families: Pregnancy-specific hormones/cytokines at the maternal-fetal interface - Soares Michael J (BMC, 2004)
Abstract The prolactin (PRL) and growth hormone (GH) gene families represent species-specific expansions of pregnancy-associated hormones/cytokines. In this review we examine the structure, expression patterns, and biological actions of the pregnancy-specific PRL and GH families.